Biological potential of plant pathogenic fungi on weeds: A mini-review essay - Kabashi, Besarta; Massimi, Mohunnad; Radócz, László (Acta Agraria Debreceniensis, 2024)
The invasion of weeds into productive areas has substantial negative effects on native ecosystems as well as agricultural production systems globally. Consequently, the task of maintaining or restoring these systems will become increasingly challenging without consistent, ongoing management efforts. The intensifying emergence of herbicide resistance in numerous weed species, coupled with the unintended pollution caused by synthetic herbicides, underscores the growing necessity for alternative, environmentally friendly, and sustainable management techniques, such as the utilisation of bioherbicides. Plant pathogenic microbes play an important role in biologically management of weeds, with the utilization of plant pathogenic fungi emerging as a promising area of study for novel research trends aimed at weed management without reliance of herbicides and to mitigate environmental pollution. A potential solution to decreasing pesticide usage involves the development of bioherbicides containing fungal active ingredients. Among the most commonly utilised fungi in bioherbicides are genera like Alternaria, Colletotrichum, Cercospora, Fusarium, Phomopsis, Phytophthora, Phoma, and Puccinia. Increased weed resistance to herbicides has influenced new strategies for weed management, with some fungi from genera such as Colletotrichum and Phoma already employed for weed control. Nonetheless, it is evident from reviews that further research is imperative in this domain, with particular emphasis on analysing the efficacy of each plant pathogenic fungi.